2020
DOI: 10.1177/1744806920936502
|View full text |Cite
|
Sign up to set email alerts
|

Differential methylation and expression of genes in the hypoxia-inducible factor 1 signaling pathway are associated with paclitaxel-induced peripheral neuropathy in breast cancer survivors and with preclinical models of chemotherapy-induced neuropathic pain

Abstract: Background Paclitaxel is an important chemotherapeutic agent for the treatment of breast cancer. Paclitaxel-induced peripheral neuropathy (PIPN) is a major dose-limiting toxicity that can persist into survivorship. While not all survivors develop PIPN, for those who do, it has a substantial negative impact on their functional status and quality of life. No interventions are available to treat PIPN. In our previous studies, we identified that the HIF-1 signaling pathway (H1SP) was perturbed between breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 144 publications
(234 reference statements)
0
46
0
Order By: Relevance
“…Utidelone and capecitabine may be associated with damage to dorsal root ganglion (DRG) neurons via energy failure or transport deficits, similar to oxaliplatin and taxane. Some studies suggested that oxaliplatin and taxane were associated with a dose-dependent reduction in plasma nerve growth factor (NGF), an essential mediator of the activity of DRG neurons (16)(17)(18)(19)(20)(21). GM1 was approved as a neuroprotective agent against excitotoxic agents and ischemia with the mechanism of modulating neuronal plasticity and memory formation.…”
Section: Discussionmentioning
confidence: 99%
“…Utidelone and capecitabine may be associated with damage to dorsal root ganglion (DRG) neurons via energy failure or transport deficits, similar to oxaliplatin and taxane. Some studies suggested that oxaliplatin and taxane were associated with a dose-dependent reduction in plasma nerve growth factor (NGF), an essential mediator of the activity of DRG neurons (16)(17)(18)(19)(20)(21). GM1 was approved as a neuroprotective agent against excitotoxic agents and ischemia with the mechanism of modulating neuronal plasticity and memory formation.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of PNS and CNS neuroinflammatory and neuroimmune processors on CIPN are being increasingly considered [ 37 , 57 , 76 ]. Many chemotherapeutic compounds, including paclitaxel, increase the serum levels of cytokines and monocytes in patients [ 77 , 78 ] and pre-clinical CIPN models. Evidence suggests that chemotherapeutic agents alter both the innate and adaptive immune responses.…”
Section: Pathophysiology Of Cancer Treatment-related Pain Syndromesmentioning
confidence: 99%
“…Work has already begun in symptoms science research to utilize a MS-DIMO analysis. In Box 1, we present three case exemplars that used a MS-DIMO analysis and discuss how this approach strengthened the study findings (Hong et al, 2018; Kober et al, 2020; Saligan et al, 2018).…”
Section: Case Exemplars Of Ms-dimo Analyses In Symptom Sciencementioning
confidence: 99%